The influence of familiarity and customer involvement on customer service experience in Malaysian public higher education industry / Mazlina Mamat, Cheam Chai Li and Nik Nor Hasimah Nik Ismail - Mamat, Mazlina; Cheam, Chai Li; Nik Ismail, Nik Nor Hasimah (Research Management Institute (RMI), 2013)
In this ever changing business environment, organizations need to create unique offerings to their customers. Creating superior customer experiences seems to be one of the central objectives in today's service environments. Firms around the globe have embraced the concept of customer experience management, with many incorporating the idea into their mission statements. A recent IBM report identifies customer service experience as a key factor for companies to use in building loyalty to brands, channels and services (Badgett, Boyce, and Kleinberger, 2007). Similarly, it has been argued that the success of Starbucks is based on creating a distinctive customer experience for their customers (Michelli, 2007). When organizations incorporating the concept of customer service experience their strategies, they need to focus on their internal sources such employees, the people who bring the organization alive and who are responsible for the output. Without the employees the organizations would be just a structure made of steel, iron, and glass. Employees are the most important asset the company has. Employee satisfaction levels can affect the quality of service, and therefore are believed to be related to customer satisfaction issue in the service industry, where front line employees have constant interaction with customers and can affect the overall company's profitability and success.